Contorted heteroannulated tetraareno(a,d,j,m)coronenes [data] - Yang, Xuan; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
Cata-condensed heteroannulated tetraarenocoronenes with C2h symmetry have been obtained from three doubly brominated diarenoperylenes. X-ray diffra...
Im Titel steht der Ausdruck "a,d,j,m" in eckiger Klammer
Gesehen am 07.03.2022
Keywords: Forschungsdaten; Datenbank